Investigating the compressibility and flowability of cocoa powders: a solution for chocolate industry - Ali, Muhammad Azhar; Shaari, Nor Shazwani; Yamin, Muhammad; Sahar, Amna; Yusof, Yus Aniza (Wiley-Blackwell Publishing, 2023)
The flowability and compressibility properties were determined for two types of cocoa powders, which are used commercially in chocolate industries; alkalized and natural cocoa powders. Physical and flow properties have a very significant role in the flow behavior, which relates to the handling, transportation, and storage of bulk powders. Throughout the research, it was observed that the properties of both cocoa powders are similar. The objectives of this work are to compare the compressibility and flowability between alkalized and natural cocoa powders and to design the minimum opening size of hopper for mass flow based on their flow properties. Jenike's mathematical methodology is applied during the research for the design of conical hoppers for mass flow. Besides, powder flow analysis using powder flow analyzer is one of the testing methodologies in this research. In addition, direct shear box tests were performed with three different normal stresses. The alkalized cocoa powder needs 1.366 m in diameter for the opening of the hopper, while the natural cocoa powder needs 1.531 m. From the results of the study conducted, it was concluded that both cocoa powders are very cohesive and have poor flow properties. This research reveals that the physical and flow properties of two main types of cocoa powder contributed a lot to the process of hopper design, enhance process understanding, and also applicable for analyzing the powder behavior at any stage in industry. Practical applications: Cocoa powder is the essential ingredient of chocolate manufacturing and other food industry having a chocolate‐like flavor including beverages, biscuits, desserts, and so forth. In chocolate industry, the flow behavior of cocoa powders can affect manufacturing efficiency, which directly affects the production capacity and product quality in terms of its weight and content uniformity. In this study, the critical design parameters such as hopper angle and size of opening were determined to improve the flowability of cocoa powders when passes through hopper. The findings of the present study make it possible for an accurate estimation of a correct intersection with the hopper flow factor line and effective angle of internal friction (δ), extrapolating the powder flow function ff curve to obtain hopper opening size for each cocoa powder for better flowability.